THE REPRESENTATION OF NATIVE AMERICAN IN THE LONE RANGER FILM: A GENETIC STRUCTURALISM ANALYSIS - Pratiwi, Dyani Prades (Lire Journal (Journal of Linguistics and Literature), 2023)
Racism is part of America's dark history. Racism seems to have never been resolved. This article examined how racism is narrated in The Lone Ranger Film. As genetic structuralism studies, The Lone Ranger film is exploited both intrinsically and extrinsically. At first glance, this film features American-Indian characters but with a white character. This is contradictory considering that American Indians are Native American tribes who have colored skin. Therefore, this film is used as an object of study to look at social construction, especially about Native Americans, which actually wants to be conveyed to the wider community, and the empirical reasons for this construction are shown. The research results showed that intrinsically, the character Tonto, played by Johnny Depp (a white), correlated to the economic purpose. As a mass culture, this film was produced to gain profits. choosing John Depp is a form of strategy to achieve the film's success because Johnny Depp is one of the top actors who has many fans. Portraying characters using well-known actors is one of the strategies for achieving the success of a film. Furthermore, this film showed how Native Americans are reconstructed by a new image. White and smart Americans are positive stereotypes. It is contradictive due to This is very contradictory considering that Native Americans are a group that has a negative stereotype. Native Americans are also a minority that experiences a lot of discrimination, especially from white or European-American groups. In conclusion, the stereotype of native Americans in the film Lone Ranger is constructed in different stereotypes showing how the whites (European-Americans) have always occupied a high position in the social strata. This film shows that Native Indians can have the same position in the social strata if their skin is colorless. This makes racism actually perpetuated through this film.